CoNiO2 as a novel water oxidation cocatalyst to enhance PEC water splitting performance of BiVO4. Issue 64 (13th July 2020) - Fang, Guozhen; Liu, Zhifeng; Han, Changcun; Ma, Xinguo; Lv, Hui; Huang, Chuyun; Cheng, Zhengwang; Tong, Zhengfu; Wang, Pan
Abstract : A strategy is proposed using CoNiO2 as a novel water oxidation cocatalyst for modification of a BiVO4 photoanode to improve the photoelectrochemical water splitting performance. Abstract : A strategy is proposed for modifying BiVO4 photoanode with CoNiO2 as a novel water oxidation cocatalyst to enhance PEC water splitting performance. The results show that CoNiO2 has the following functions: reducing photogenerated charge recombination centers; providing trapping sites to promote charge separation; improving the stability of the overall system; providing more active sites; and offering a lower overpotential. The BiVO4 /CoNiO2 photoanode has a higher photocurrent density (1.16 mA cm −2 at 1.23 V vs. RHE), a lower onset potential (∼0.06 V vs. RHE), a larger IPCE (34.37%) and ABPE (0.163%), better stability and good rates of hydrogen evolution (0.0148 μmol cm −2 min −1 ) and oxygen evolution (0.0076 μmol cm −2 min −1 ). The strategy provides promising prospects for achieving efficient PEC water splitting performance using water oxidation cocatalysts.